SUPERVISI KLINIS DALAM MENINGKATKAN KUALITAS MENGAJAR GURU MADRASAH IBTIDAIYAH - Sulani Sulani; Reza Liana; Khairiah Khairiah (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2022)
The quality of teaching madrasah ibtidaiyah teachers has not been optimal because clinical supervision plays a maximum role. The purpose of this paper is to map and analyze clinical supervision in improving the quality of teaching madrasah ibtidaiyah teachers. Using qualitative methods of descriptive analysis with three descriptive, explanatory and interpretive steps. The results can be concluded that the quality of teaching teachers is influenced by the implementation of clinical supervision, because the implementation of clinical supervision can improve the pedagogical competence of teachers, maximizing the follow-up program of clinical supervision results. Clinical supervision is part of teaching supervision, and clinical supervision emphasizes looking for weaknesses and causes of problems that occur in the learning process and striving for improvements to these weaknesses, so that teachers have a sense of security, and are willing to improve teaching behavior with full awareness and awareness. The quality of teaching teachers can be realized through clinical supervision because clinical supervision focuses on efforts to improve the learning process, and clinical supervision is professional assistance given to teachers who experience obstacles in carrying out learning so that the teacher can overcome the problems he experiences related to the learning process. Thus the author can warn if you want to improve the quality of teaching teachers then increase clinical supervision of madrasah Ibtidaiyah teachers.